The nature of interactions in Alkylimidazolium based ionic liquids - Sinxi, Monde (Department of Chemistry, 2016)
Ionic liquids are materials that have the ability to be designed for specific tasks. Their properties can be adjusted by changing the molecular constituents of the liquid or the intermolecular interactions between composite ions through functionalisation. Therefore, understanding the nature of the interactions between ions is important. In the thesis, we use density functional theory calculations to obtain conformers of 1-ethyl-3-methylimidazolium ([emim]+)paired with the anions [Cl]-, [Br]-, [MeCO2]-, [CF3CO2]-, [MeSO3]-, [CF3SO3]-, [BF4]- and [PF6]-. We analyse the structures of the pairs and then explore the nature of the electrostatic, dispersion and hydrogen bonding interactions. Electrostatic interactions were the most dominant interactions. The dispersion interaction energies were found to be of the same order as the estimated energy of the hydrogen bond. The non-covalent index (NCI) analysis was used to visualise the non-covalent interactions in real space as enclosed surfaces. The properties of the surfaces were used to characterise interaction types, namely van der Waals interactions and hydrogen bonds. Furthermore, we find that the density enclosed within the hydrogen bonding surfaces can be used to estimate the potential of the hydrogen bond. To our knowledge, a potential for hydrogen bonding from NCI has not been explored for ionic liquids. Finally, the average strength of the hydrogen bond was calculated from structures extracted from molecular dynamics simulations. They reveal that the hydrogen bond strength for [emim][MeCO2] is approximately two-thirds weaker in the condensed phase than in the gas phase. The effect of the polarising environment is also found to weaken the hydrogen bond slightly.